2020
DOI: 10.1097/tp.0000000000003129
|View full text |Cite
|
Sign up to set email alerts
|

Patient Travel Distance and Post Lung Transplant Survival in the United States: A Cohort Study

Abstract: Background. In response to a longstanding Federal mandate to minimize the role of geography in access to transplant in the United States, we assessed whether patient travel distance was associated with lung transplant outcomes. We focused on the posttransplant time period, when the majority of patient visits to a transplant center occur. Methods. We present a cohort study of lung transplants in the United States between January 1, 2006, and May 31, 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…They found that distant travelers had better outcomes compared to nontravelers 14 . In a retrospective single‐center study, Tsuang et al 15 found no significant relationship between recipient travel distance and post lung transplant graft survival. They concluded that in carefully selected recipients, travel distance is not a significant barrier to successful posttransplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They found that distant travelers had better outcomes compared to nontravelers 14 . In a retrospective single‐center study, Tsuang et al 15 found no significant relationship between recipient travel distance and post lung transplant graft survival. They concluded that in carefully selected recipients, travel distance is not a significant barrier to successful posttransplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The LAS is a quantitative measure of medical urgency used to prioritize waitlisted patients using over a dozen clinical variables 21 . Patient driving distance was calculated using the methods we have previously described 22 . We also assessed whether a national policy shift toward broader geographic sharing of donor's lungs during the study period 23 impacted our results (pre‐ vs. post‐November 2017).…”
Section: Methodsmentioning
confidence: 99%
“…21 Patient driving distance was calculated using the methods we have previously described. 22 We also assessed whether a national policy shift toward broader geographic sharing of donor's lungs during the study period 23 impacted our results (pre-vs. post-November 2017).…”
Section: Model Covariatesmentioning
confidence: 99%
“…This study was declared exempt by the Cleveland Clinic Institutional Review Board (19‐1432). Portions of this study were presented at the American Transplant Congress, 10 and our approach using Google Maps has been described in a separate publication on posttransplant outcomes 11 …”
Section: Methodsmentioning
confidence: 99%
“…Portions of this study were presented at the American Transplant Congress, 10 and our approach using Google Maps has been described in a separate publication on posttransplant outcomes. 11 We linked the SRTR with additional registries to include the median annual income for each zip code as captured by the US Census, 12 the metro population size from the US Department of Agriculture, 13 and the Distressed Communities Index (DCI) from the Economic Innovation Group. 14 The DCI combines metrics such as unemployment, education level, poverty rate, median income, and housing vacancies in order to calculate an index score for each zip code from 0 (no distress) to 100 (severe distress).…”
Section: And May 31 2017 In the Scientific Registry Of Transplantmentioning
confidence: 99%